Physiological and lifestyle factors contributing to risk and severity of peri-orbital dark circles in the Brazilian population - Mary S Matsui; Sérgio Schalka; Garrett Vanderover; Christina G. Fthenakis; J Christopher; Patricia Camarano Pinto Bombarda; Juliana Regina Bueno; Bianca Lenci Inácio Viscomi; Mário Sérgio Bombarda Júnior (Sociedade Brasileira de Dermatologia, 2015)
AbstractBACKGROUND:Peri-orbital dark circles are a cosmetic concern worldwide, and have been attributed to hyperpigmentation from allergy or atopic dermatitis, blood stasis, structural shadowing effects, and a thin epidermis/dermis under the eye. It is of interest to better understand lifestyle and demographic risk factors and the relative impact of melanin, blood and epidermal/dermal factors on the severity of Peri-orbital dark circles.OBJECTIVE:To compare by non-invasive imaging the impact of biological factors to a visual grading scale for Peri-orbital dark circles, and test the correlation of various demographic factors with Peri-orbital dark circles.METHODS:Subjects completed a lifestyle and health survey, and Peri-orbital dark circles severity was evaluated using standardized photographs. Hyperspectral image analysis was used to assess the contributions of melanin, blood volume, degree of blood oxygen saturation, and dermal scattering.RESULTS:Family history was the most significant risk factor for Peri-orbital dark circles. The average age of onset was 24 years, and earlier onset correlated with higher severity scores. Asthma was significantly associated with Peri-orbital dark circles scores, but self-reported allergy was not. In this study, sleep was not correlated with Peri-orbital dark circles scores. Hyperspectral imaging indicated that melanin was the dominant correlate for Peri-orbital dark circles severity, while oxygen saturation was secondary. The difference between under-eye and cheek measurements for ΔL*and ΔE* were the most significant instrumental parameters correlated with visual assessment of Peri-orbital dark circles severity.CONCLUSION:Although typically associated with lack of sleep, risk of Peri-orbital dark circles is primarily hereditary. The main factors contributing to the appearance of Peri-orbital dark circles are melanin and (deoxygenated) blood.